Patterns of heavy drinking behaviour over age and birth cohorts among Chinese men: a Markov model - Joshua Salomon; Kyueun Lee; Jeremy Goldhaber-Fiebert (BMJ Open)
Objectives To estimate the age patterns and cohort trends in heavy drinking among Chinese men from 1993 to 2011 and to project the future burden of heavy drinking through 2027.Design We constructed a Markov cohort model that simulates age-specific heavy drinking behaviours for a series of cohorts of Chinese men born between 1922 and 1993 and fitted the model to longitudinal data on drinking patterns (1993–2015). We projected male prevalence of heavy drinking from 2015 through 2027 with and without modification of heavy drinking behaviours.Participants A cohort of Chinese men who were born between 1922 and 1993.Main outcome measures Outcomes included age-specific and birth cohort-specific rates of initiating, quitting and reinitiating heavy drinking from 1993 through 2011, projected prevalence of heavy drinking from 2015 to 2027, and total reduction in prevalence and total averted deaths with hypothetical elimination of heavy drinking behaviours.Results Across multiple birth cohorts, middle-aged Chinese men have consistently higher risks of starting and resuming heavy drinking and lower probabilities of quitting their current heavy drinking than men in other age groups. From 1993 to 2011, the risk of starting or resuming heavy drinking continued to decrease over generations. Our model projected that the prevalence of heavy drinking among Chinese men will decrease by 33% (95% CI 11.5% to 54.6%) between 2015 and the end of 2027. Complete elimination of or acceptance of a change in heavy drinking behaviours among Chinese men could accelerate this decrease by 12 percentage points (95% CI 7.8 to 18.2) and avert 377 000 deaths (95% CI 228 000 to 577 000) in total from 2015 to 2027.Conclusion Heavy drinking prevalence will continue to decrease through 2027 if current age-specific and birth cohort-specific patterns of starting, quitting and resuming heavy drinking continue. Effective mitigation policy should consider age-specific patterns in heavy drinking behaviours to further reduce the burden of heavy drinking.